Case reports of improvement in behaviour following switching of patients with intellectual disability and epilepsy from levetiracetam to brivaracetam. Issue 3 (7th April 2020) - Baburaj, Raghavendar; Dunstall, Huw Morgan; Bright, Catherine; Lawthom, Charlotte
Abstract : Purpose: Epilepsy is a chronic illness affecting around 50 million people worldwide. Levetiracetam is an effective novel antiepileptic drug but can cause behavioural adverse events. A total of 10-15 per cent people with intellectual disability (ID) already present with Behaviour that Challenges (BtC). Brivaracetam is postulated to have a distinct pharmacological profile compared with levetiracetam which may result in fewer behavioural adverse events. Design/methodology/approach: This paper presents two cases of people with epilepsy and ID being switched from levetiracetam to brivaracetam for reported behaviour adverse events. Findings: The cases support that people with epilepsy and ID who are experiencing behavioural adverse events from levetiracetam can safely be switched to brivaracetam, resulting in significant reductions in BtC and potentially improved seizure control. Nevertheless, these results must be interpreted with caution, as aetiology for BtC in people with ID is often multifactorial. Originality/value: This is one of the first papers to date, according to the best of the authors' knowledge, to describe improved behavioural profile in people with ID and epilepsy when switching from levetiracetam to brivaracetam.